Temperate and boreal forest mega‐fires: characteristics and challenges. Issue 2 (15th January 2014) - Stephens, Scott L; Burrows, Neil; Buyantuyev, Alexander; Gray, Robert W; Keane, Robert E; Kubian, Rick; Liu, Shirong; Seijo, Francisco; Shu, Lifu; Tolhurst, Kevin G; van Wagtendonk, Jan W
Abstract : Mega‐fires are often defined according to their size and intensity but are more accurately described by their socioeconomic impacts. Three factors – climate change, fire exclusion, and antecedent disturbance, collectively referred to as the "mega‐fire triangle" – likely contribute to today's mega‐fires. Some characteristics of mega‐fires may emulate historical fire regimes and can therefore sustain healthy fire‐prone ecosystems, but other attributes decrease ecosystem resiliency. A good example of a program that seeks to mitigate mega‐fires is located in Western Australia, where prescribed burning reduces wildfire intensity while conserving ecosystems. Crown‐fire‐adapted ecosystems are likely at higher risk of frequent mega‐fires as a result of climate change, as compared with other ecosystems once subject to frequent less severe fires. Fire and forest managers should recognize that mega‐fires will be a part of future wildland fire regimes and should develop strategies to reduce their undesired impacts.